Lack of motivation in a group of tenth graders taking an intermediate level course of business english - Kruse Quirós, Eugenia 1958- (2012)
The main purpose of this research was to analyze how the lack of motivation affects academic performance in a group of fifteen 10 th graders from the Humboldt School, Costa Rica, taking an intermediate level Business English course. Data were collected by using an instrument to measure perceived importance of high school subjects in order to determine if motivation is affected by the importance students give to the different language courses they take. The Rosenberg Self-Esteem Scale, a universal tool of self-esteem measurement widely used with adolescents and young adults, was applied to find out if a low self-esteem would affect the students' motivation to learn; interviews to two students and a teacher of both of them were also used as data collection instruments. An end-of-the-course questionnaire was used to confirm the results of the previous instruments and to validate sorne of the presumptions that led to the investigation. This study sought to find any possible correspondence between these aforementioned factors and a low academic outcome. Results are congruent with the expectations since these students, in general, have lower self-esteem and lower academic achievement than a parallel group used as reference.